2019
DOI: 10.1016/j.jplph.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Plant selenium toxicity: Proteome in the crosshairs

Abstract: The metalloid element, selenium (Se) is in many ways special and perhaps because of this its research in human and plant systems is of great interest. Despite its non-essentiality, higher plants take it up and metabolize it via sulfur pathways, but higher amounts of Se cause toxic symptoms in plants. However, the molecular mechanisms of selenium phytotoxicity have been only partly revealed; the data obtained so far point out that Se toxicity targets the plant proteome. Besides seleno-and oxyproteins, nitroprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 107 publications
(83 reference statements)
0
33
0
Order By: Relevance
“…The role of Se in higher plant metabolism and its essentiality still needs more evidences (Pilon-Smits, 2019). Several reports confirmed that Se can stimulate the growth and plant quality at low applied concentration (Golubkina et al, 2018), improve the photosynthesis rate (Jiang et al, 2017amd Zsiros et al, 2019, and strengthen the plant defense under stress (Bocchini et al, 2018;Hawrylak-Nowak et al, 2018;Singh et al, 2018 andKolbert et al, 2019). On the other hand, nano -selenium (nano-Se) or selenium nanoparticles (Se-NPs) has also distinguished features including low toxicity and high bioactivity comparing with other Se-forms like selenate or selenite or selenomethionine (Djanaguiraman et al, 2018).…”
Section: Introductionmentioning
confidence: 93%
“…The role of Se in higher plant metabolism and its essentiality still needs more evidences (Pilon-Smits, 2019). Several reports confirmed that Se can stimulate the growth and plant quality at low applied concentration (Golubkina et al, 2018), improve the photosynthesis rate (Jiang et al, 2017amd Zsiros et al, 2019, and strengthen the plant defense under stress (Bocchini et al, 2018;Hawrylak-Nowak et al, 2018;Singh et al, 2018 andKolbert et al, 2019). On the other hand, nano -selenium (nano-Se) or selenium nanoparticles (Se-NPs) has also distinguished features including low toxicity and high bioactivity comparing with other Se-forms like selenate or selenite or selenomethionine (Djanaguiraman et al, 2018).…”
Section: Introductionmentioning
confidence: 93%
“…As the genetic mechanism(s) of fungal Se reduction are currently unknown, the reduction pathways are not yet fully understood. Some toxicology studies suggest that Se(IV) is more toxic than Se(VI) in plants (e.g., Kolbert et al, 2018;Molnár et al, 2018), which could be the case for fungi as well. As such, the mechanisms for Se(IV) detoxification may be very effective and efficient, particularly at higher Se loadings.…”
Section: Assessing and Improving The Se Mycoremediation Potentialmentioning
confidence: 99%
“…In general, the content of Se in plant tissues caused toxicity is around 5 mg kg −1 dry weight. The Se tolerance range in crop plants are quietly different, for instance, in rice 2 mg kg −1 dry weight is the maximum levels of Se, in wheat is 4.9 mg kg −1 dry weight, while Dutch clover can tolerant 330 mg kg −1 dry weight (Kolbert et al, 2018). Based on these results, we suggested that a relatively higher dosage of Se-compounds may cause cell toxicity and induce inflammation by increasing COX-2 expression.…”
Section: Discussionmentioning
confidence: 84%